Ultrafast spectroscopic investigation of the effect of solvent additives on charge photogeneration and recombination dynamics in non-fullerene organic photovoltaic blends. Issue 20 (24th April 2020) - Yang, Qingqing; Li, Xitong; Tang, Hao; Li, Youzhan; Fu, Yingying; Li, Zhanguo; Xie, Zhiyuan
Abstract : The effects of DIO and CN additives on the neat and PBDB-TF :IT-4F blend film morphologies and the related ultrafast photophysical processes are studied. Abstract : The PBDB-TF :IT-4F blend is a kind of state-of-the-art non-fullerene photovoltaic blend. Herein, the effects of 1, 8-diiodooctane (DIO) and 1-chloronaphthalene (CN) additives on the neat and blend film morphologies and the related ultrafast photophysical processes are studied. It is found that both DIO and CN can lead to an enhanced structural order in the in-plane direction and increased average lifetime of excitons in neat PBDB-TF films. The face-on orientation of PBDB-TF still exists in the DIO-processed PBDB-TF :IT-4F blend film, while in the case of the CN-processed blend film, molecular packing orientation is similar to that of the pristine blend film. The blend samples prepared with the two additives show increased initial exciton yields. Interestingly, in the blend samples prepared with the DIO additive, the recombination loss via the formation of polymer triplet excitons can be effectively suppressed, in comparison to the pristine and CN-processed samples. Both the DIO- and CN-processed devices show increased short-circuit current densities. The DIO-processed device is also found to have a superior fill factor due to suppressed recombination loss. The work provides a comprehensive insight into the ultrafast photophysical processes in varied blend morphologies induced by additives and their effect on the photovoltaic parameters of the devices.